Facebook-infused Identities: Learners' Voices - Mohd Muzhafar Idrus; Ruzy Suliza Hashim; Imran Ho-Abdullah; Noraini Md Yusof; Raihanah Mohd Mydin; Shahizah Ismail Hamdan (Canadian Center of Science and Education, 2024)
The National Higher Education Strategic Plan of Malaysia focuses on graduates who are innovative and knowledgeable to meet the standards and challenges of 21st century. This paper, then, explores how an innovation practice has taken place in a course entitled “Gender Identities: Malaysian Perspectives” where students scrutinize gender across Facebook “texts,” as opposed to using literary texts. By using Facebook as baseline data to analyze online gender construction, students have learned the ways in which cyberspace deconstructs certain parameters of identity construction. Following this premise, this article discloses how students analyze gender identities. They analyze Facebook accounts of a male educator in United States, a female Malaysian college instructor residing in United States, and a law/politics Malaysian undergraduate. Firstly, the students revealed that identity in Facebook spaces is shown through genuine names and profile pictures; rightfully so for job, networking, and relationship purposes. Secondly, by selecting specific audiences, negotiating identities of a friend, co-worker, lover and most importantly future employee in Facebook is a difficult task. Conflicts usually occur while “masking” certain information on Facebook as they go about connecting with friends, students, parents, and prospective partners. Thirdly, societal constraints limit opposite gender’s approval of friend requests. Lastly, identity construction reveals that having voices and emotions on Facebook have both positive and negative implications. Pedagogical recommendations are also presented as a result of this inclusion of Facebook in literature classrooms.